Aid allocation, selectivity, and the quality of governance - In’airat, Mohammad (2014)
The introduction of good governance in the economic growth and development agenda in the last two decades, along with the failure of aid conditionality to produce positive growth results, motivated expost selectivity instead of the ex-ante conditionality as a new approach to aid allocation. This paper aims to explore whether aid selectivity on the basis of the quality of governance is employed as a criterion in foreign aid allocation. The paper uses different instrumental variables as estimators to analyze the determinants of aid allocation over the period 2001–2010. The results produced strong evidence that countries with good governance are given preferential treatment by donors. Among the six governance indicators, it seems that voice and accountability and control of corruption are critical in the aid allocation decision. DOI: http://dx.doi.org/10.1016/j.jefas.2014.03.002